FACEBOOK: FROM PERSONAL MEDIUM TO MASS MEDIUM – AND BACK AGAIN? - THE USE OF FACEBOOK ACROSS AGE GROUPS 2015-19 - Jensen, Jakob Linaa (AoIR Selected Papers of Internet Research, 2020)
This paper investigates how different age groups perceive Facebook as a personal medium and a mass medium, respectively, based on a time series analysis of Danish Internet users. As Denmark for long has been one of the countries with relatively most Facebook users and as Facebook plays an important role in everyday life and the public debate, data from Denmark might give good indications of Facebook’s development in general. This paper is based on five consecutive surveys among Danish Internet users, in 2015, 2016, 2017, 2018 and 2019 (N between 1200 and 1500 each year). I focus on the use of different parts of Facebook across age groups; the personalized uses like Messenger, private groups and intimate communication, versus “mass media use” like reading news, organizational and political information and taking part in nationwide debates. I also investigate different age groups’ attitudes towards Facebook and whether they see it as a personal or a mass medium. First and foremost, I find notable differences across age groups. I also find that the differences are increasing over the years. In 2015 there were not significant differences in Facebook use across age groups. In 2019 a vast majority of the youngest, aged 18-30, used Facebook dominantly as a personalized medium, highlighting Messenger and private groups as their preferred ways of communication and interaction. The older generations have a much more diversified use, treating Facebook as a personal as well as a mass medium.